Institutional Trust and Citizen Support for the Government Socioeconomic Policy in the Early Phase of the COVID-19 Pandemic in the Republic of Moldova - Negură, Petru; Gașper, Lucia; Potoroacă, Mihai (Calitatea Vieții, 2022)
This paper analyses the citizens’ attitudes and support for the government initiatives aiming to mitigate the socioeconomic impact of the early phase of the Covid-19 pandemic in Moldova. It draws on mixed method research carried out in the Republic of Moldova, in June and July 2020, by a questionnaire conducted with a nationally representative sample (n=1202), and a qualitative survey utilizing in-depth interviews (n=95). The respondents of the questionnaire survey share high dissatisfaction with the way the authorities managed the Covid-19 pandemic and its socioeconomic impact. Respondents with more confidence in state institutions are more satisfied with the way the government managed the pandemic and its effects. Participants in the qualitative survey through interviews highlighted several gaps and inconsistencies in the way the authorities managed the pandemic and its impact on people’s life. The actions or inactions of the authorities might further undermine citizens’ trust in state institutions and in the official interpretation of events. The “pro-business and pro-citizens” measures announced by the government of Moldova on 1 April 2020, in a context strongly influenced by the presidential elections, which took place in November 2020, proved to be modest and little effective. The support measures assumed by the Moldovan government for businesses and employees represented 1.2% of GDP, which is extremely low, compared to the support provided to enterprises and employees in Western countries and in countries from the region.